1981
DOI: 10.1159/000207177
|View full text |Cite
|
Sign up to set email alerts
|

‘Early’ Splenectomy and Survival in Agnogenic Myeloid Metaplasia

Abstract: The data available for 338 cases of splenectomy in agnogenic myeloid metaplasia published since 1940 were retrieved from the literature and analyzed. The median survival of cases operated upon at an early stage of the disease (as judged by their hemoglobin level, platelet number, and splenic size) was compared with the survival reported in conservatively treated patients diagnosed at an early stage of agnogenic myeloid metaplasia. Survival time since diagnosis of patients with early splenectomy was similar to,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

1987
1987
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 3 publications
1
7
0
Order By: Relevance
“…In the present series a Hb-concentration > 10 g/dl was associated with a favourable prognosis and both in the univariate and the multivariate analysis the Hb-concentration consistently emerged as an important prognostic parameter, being in accordance with previous observations (10)(11)(12)(13)(14)(15)(16)(17)(18)(19).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present series a Hb-concentration > 10 g/dl was associated with a favourable prognosis and both in the univariate and the multivariate analysis the Hb-concentration consistently emerged as an important prognostic parameter, being in accordance with previous observations (10)(11)(12)(13)(14)(15)(16)(17)(18)(19).…”
Section: Discussionsupporting
confidence: 92%
“…Several reports on idiopathic myelofibrosis (IMF) have shown that the clinical course and prognosis are extremely variable, with median survival times from diagnosis ranging from 1.4 to 5.2yr (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Results of complex ferrokinetic isotope studies on the site and function of erythropoiesis and measurements of total red cell and plasma volumes have been conflicting with regard to their prognostic significance (19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…As in 2 patients of the present series, it has been re ported previously that in some IM patients the in crease in hepatic myeloid metaplasia following sple nectomy can be so massive as to provoke prominent clinical and biological signs of liver dysfunction, even leading to death [10,14,15,18,19]. The reason why some patients develop this overwhelming complica tion is not known, and no preoperative clinical or lab oratory data have been found that predict this course [ …”
Section: Discussionmentioning
confidence: 67%
“…It is still unknown whether splenectomy alters the natural history and prognosis of patients with PMF as no controlled randomized trials have been performed. A retrospective analysis of the effects of splenectomy performed early in the course of the disease showed that the survival of splenectomized patients was similar to, or even shorter than, that of patients treated conservatively (Benbassat & Penchas 1981). Although a policy of early elective splenectomy has its protagonists (Crosby 1972;Mulder et al 1977), it has thus not been widely adopted.…”
Section: Splenectomymentioning
confidence: 99%